D’Ángel Rodríguez Leira à Ángel Cariño López - Óscar Freán Hernández (Cahiers de Civilisation Espagnole Contemporaine)
This article will analyse the journey of an anti-fascist fighter who, fleeing Franco’s Spain, continued the fight against Nazism in North Africa and Europe and ended up in France, where he settled and lived until his death, without ever returning to Galicia. Like so many other exiles, the fate of our protagonist is marked by the Civil War and the Second World War, by the separation from his family and his country, by the reconstruction of a new life in France, by silence and by the presence of a complex and difficult past.